Analisis Kompetensi Profesional dan Kompetensi Pedagogik Mahasiswa Pendidikan Ekonomi Universitas Negeri Padang - Eka Deasi Sri Wulan Dari; Yulhendri Yulhendri (Universitas Negeri Padang, 2019)
This study aims to analyze professional competence and pedagogic competence students of economic education of Padang State University. This type of research is descriptive research. The population of this research is the economic education of the force of 2016 Faculty Economics of Padang State University. Components of 119 students, this research sample amounted to 55 students. Data are collected by documentation, and test. The results of this study indicate: professional competence and pedagogics students of economic education force 2016 that will carry out the PLK in less category and enough professional competence consists of mastering concept structure material and science mindset that supports the subjects that are infected, developing creative learning materials are created. For pedagogic competence consists of mastering the learning theory and educational principles of education; Developing curriculum related to the field of development is promoted; Mastering the characteristics of learners from physical, moral, social, cultural, emotional, and intellectual aspects; Utilizing the results of the assessment and evaluation for the learning interests. Keyword: professional competence, pedagogic competence